Management of aortic stenosis in pregnancy - Pecoraro, A.J.K. (SA Heart Journal, 2017)
Aortic stenosis in pregnancy is most commonly related to congenital or bicuspid aortic stenosis, which is associated with an aortopathy and ascending aortic dilatation. The management of AS in pregnancy is based on a few key principles. First and foremost the accurate assessment of the patient’s symptoms and confi rmation, via echocardiography, of the degree of AS is of the utmost importance. Exercise testing is a very handy adjunct to quantify symptoms. Based on these fi ndings, an informed process of discussion between the patient and a multidisciplinary team will lead to the correct management. As a general rule, patients who are truly asymptomatic with normal left ventricular systolic function and normal aortic root are able to tolerate pregnancy with a low maternal and fetal risk.